Analisis Penentuan Prioritas Platform Digital untuk Mendukung Pemasaran Melon Menggunakan Metode Ahp pada Jagasura Farm Tegal - Muhamad Reyhan; Sri Lestari (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The development of digital marketing provides opportunities for agribusinesses to expand market reach through the utilization of various digital platforms. Jagasura Farm Tegal has used TikTok, Instagram, and WhatsApp in melon marketing, but does not yet have a structured basis for determining platform priorities. This study aims to determine the best digital platform to support melon marketing using the Analytical Hierarchy Process (AHP) method. The study used a quantitative descriptive approach involving 3 internal respondents and 23 consumer respondents. Data collection was carried out through interviews, observations, documentation, and questionnaires. Assessment criteria included market reach, promotion costs, ease of use, customer interaction, and sales effectiveness with alternative platforms such as TikTok, Instagram, and WhatsApp. The results showed that sales effectiveness was the main criterion with a weight of 0.4001, followed by customer interaction with 0.3138. The results of the alternative priority calculation showed TikTok as the best platform with a score of 0.5743, followed by WhatsApp with 0.2978 and Instagram with 0.1279. The Consistency Ratio (CR) value of 0.0488 indicates a consistent assessment matrix. Thus, TikTok has become the most effective platform in supporting the marketing of Jagasura Farm Tegal melons.